The short-term influence of cumulative, sequential rainfall-runoff flows on sediment retention and transport in selected SuDS devices. Issue 6 (3rd July 2019) - Allen, Deonie; Haynes, Heather; Olive, Valerie; Allen, Steve; Arthur, Scott
ABSTRACT: It is necessary to understand Sustainable urban Drainage Systems (SuDS) sediment retention efficiencies to fully comprehend SuDS pollution removal properties and urban sediment movement from source-to sink. This research presents the detention and transport of a single tagged sediment release through four SuDS devices over 12 months, with the aim of quasi-quantifying these selected SuDS devices sediment detention efficiencies. Field monitoring and mass balance analysis of deposited sediment shows that tagged sediment from the single sediment release moves through the monitored SuDS, with deposition declining over the 12-month monitoring period. Initial retention is high (>80% during the first week of monitoring) but falls below 80% after multiple consecutive rainfall-runoff events (events ≤50% ARI). The field monitoring illustrates retention to generally remain above 50%, suggesting that SuDS are highly efficient at retaining urban sediment pollution but that deposition of a single sediment release may resuspend due to cumulative rainfall-runoff events.